Evaluation of the monthly air temperature extremity for the 1961-2007 period - POKLADNÍKOVÁ, Hana; ROŽNOVSKÝ, Jaroslav; STŘEDA, Tomáš (Contributions to Geophysics and Geodesy, 2021)
For the evaluation of monthly temperature extremity of the 1961‒2007 period three stations in south Moravia (Brod nad Dyjí, Lednice and Velké Pavlovice) were chosen. The elevation of the stations is about 200 m a.s.l. and their relative distance is 11‒17 km. The mean monthly air temperature based on daily means was compared with the mean monthly air temperature of the normal-period (1961‒1990) concrete month. According to the standard deviation of the normal-period included in this difference, the extremity categories were defined. Every month was included to the defined category of extremity (extraordinary above normal, far above normal, above normal, normal, below normal, far below normal and extraordinary below normal). As extraordinary above normal 79 months, as far above normal 115 months, as above normal 175 were classified. As extraordinary below normal 32 months, as far below normal 86 and as below normal 129 were classified. Periods of 1961‒1970 and 1971‒1980 contain more cold months than the last two periods (with the prevailing warm month). This trend of warming during last 17 years is perceptible at all stations. From this study, the spatial temperature diversity is obvious even in a small area considered.